A Methodology for Cellular Manufacturing Design - Thomas Rist; Róbert Debnár; Jozef Krišťák (Communications - Scientific letters of the University of Zilina, 2000)
The realisation of benefits expected from cellular manufacturing largery depends on how effectively the three phases of design have been performed, namely part/machine grouping, developing the cell layout and cell system layout on the shop floor. This key question of cellular manufacturing has attracted numerous attempts in applying various design methods. This paper presents a new methodology for cellular manufacturing design. The proposal methodology is composed from products analysis, production segmentation, cells definition, cells capacity planning, cells layout design, building of simulation model and simulation process. Recently, simulation has been found to be a useful optimalization technique just in this area.